A Pathway of Distinction in Global Health – : A Professional Development Model to Prepare Medical Students as Future Global Health Leaders (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Infectious Diseases; Research